Preemptive Effects of Administration of Tualang Honey on Inflammatory Responses in Adult Male Rats - Che Aishah Nazariah Ismail; Che Maraina Che Hussin; Mahaneem Mohamed; Che Badariah Abd Aziz (Journal of Pharmacy and Nutrition Sciences, 2017)
Background: Honey was reported to reduce pain and inflammation from burn wound. To date, no study has compared between the effects of Tualang honey and prednisolone on inflammatory responses in rats. This study has examined the effects of Tualang honey and prednisolone on inflammatory pain and its associated inflammatory responses secondary to formalin injection. Methods: Twenty-one Sprague-Dawley male rats were randomised into control, Tualang honey (1.2 g/kg) or prednisolone (10 mg/kg)groups. Formalin test was conducted and the rats were sacrificed at four-hours post-formalin injection. Serum was collected for measurement of leukocytecounts and interleukins level. All data were analysed using one-way ANOVA with post-hoc Scheffe’s or Dunnet’s C test. Significance level was taken as less than 0.05. Results: Tualang honey and prednisolone groups had significantly reduced pain behaviour and paw edema compared to control group. Tualang honey group demonstrated a significant increase in blood neutrophil count while prednisolone group had significant reduction in blood lymphocyte and monocyte counts compared to control group. Only interleukin-6 level was significantly reduced in honey group. Both interleukin-6 and -8 levels were significantly reduced in prednisolone group. Conclusions: Tualang honey is comparable to prednisolone in modulating the inflammatory pain responses in rats; however, with regards to local and systemic inflammatory responses, it has differential effects compared to prednisolone.